The Connection between Early Mobilization and Wound Healing Time After Sectio Caesarea at Morotai Island Hospital - Fitri Priyanti; Anik Sri Purwanti; Widia Shofa Ilmiah (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Sectio caesarea (CS) is a common surgical procedure for high-risk deliveries, but one complication that may occur is slow wound healing. This can be influenced by several factors, one of which is early mobilization. Early mobilization improves blood circulation, reduces the risk of thrombosis, and accelerates wound healing. However, many post-CS mothers are hesitant to engage in early mobilization due to pain and discomfort. This study was conducted to investigate the relationship between early mobilization and the duration of wound healing in post-CS mothers at Morotai Island Hospital. An analytical cross-sectional design was used, involving 16 post-CS mothers who were selected using purposive sampling. Data collection was performed through observation, interviews, and a questionnaire, along with an examination of postoperative wound conditions. The Wilcoxon statistical test was used to assess the relationship between early mobilization and wound healing duration. The findings showed that mothers who engaged in early mobilization experienced faster wound healing compared to those who did not. The statistical test revealed a p-value of 0.000 (p < 0.05), indicating a significant relationship between early mobilization and wound healing duration. Early mobilization was shown to be an effective strategy for accelerating post-CS recovery, as mothers who mobilized early had quicker recovery times. Based on these results, it is recommended that early mobilization be integrated into postoperative care plans to improve recovery and prevent complications. Additionally, more intensive education on the benefits of early mobilization should be provided to post-CS mothers. Healthcare providers at Morotai Island Regional Hospital should offer support and motivation to encourage mothers to engage in early mobilization, ultimately aiding in faster recovery.